2014
DOI: 10.1021/ie501673v
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Solar Photocatalytic Degradation of Phenol with Coupled Graphene-Based Titanium Dioxide and Zinc Oxide

Abstract: In this study, graphene-based titanium dioxide and zinc oxide composites (TiO 2 -G, ZnO-G) were synthesized using a hydrothermal process. Materials were characterized using X-ray diffraction, X-ray photoelectron spectroscopy, Raman spectroscopy, UV−vis spectroscopy, scanning electron microscopy, and transmission electron microscopy. Photocatalytic activity of the composite materials under simulated solar light was studied using phenol as a model compound. A ca. 30% improvement on the degradation performance by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(54 citation statements)
references
References 53 publications
3
50
0
1
Order By: Relevance
“…Sengupta et al [48] used a Taylor vortex reactor (TVR) for the degradation of phenol under UV light. Chowdhury et al [7] used slurry photoreactor with dye-sensitized photocatalyst, and Malekshoar et al [5] used slurry photoreactor with graphene-based photocatalyst for phenol degradation under solar light. Studies by other researchers reported degradation of phenols with (i) TiO 2 -coatedfiber-optic cable reactor [16], (ii) tubular photoreactor [49], (iii) continuous flow photoreactor [50], and (iv) solar photoreactor (CPC modules and flat reactor) [51].…”
Section: Photoreactorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sengupta et al [48] used a Taylor vortex reactor (TVR) for the degradation of phenol under UV light. Chowdhury et al [7] used slurry photoreactor with dye-sensitized photocatalyst, and Malekshoar et al [5] used slurry photoreactor with graphene-based photocatalyst for phenol degradation under solar light. Studies by other researchers reported degradation of phenols with (i) TiO 2 -coatedfiber-optic cable reactor [16], (ii) tubular photoreactor [49], (iii) continuous flow photoreactor [50], and (iv) solar photoreactor (CPC modules and flat reactor) [51].…”
Section: Photoreactorsmentioning
confidence: 99%
“…When semiconductor photocatalyst is illuminated with light energy greater than the band gap of the photocatalyst, charge carriers (i.e., electron-hole pair) are produced which ultimately generate hydroxyl radicals (HO • ) in the system. Recently, photocatalytic degradation of phenol and phenolic compounds in wastewater has been extensively studied by several research groups [4][5][6][7][8][9][10][11][12][13]. Titanium dioxide (TiO 2 ) photocatalyst is frequently used in the degradation of phenols under ultraviolet light [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…If the lifetime is long enough, the electrons form a system which can be utilised as highly sensitive light detectors or sensors [251252]. Due to this synergetic effect via interfacial charge transfer and inhibition of recombination of excited electrons, this hybrid has wide spread applications in waste water purification by the photocatalytic degradation of dye molecules like MB [253259], rhodamine B [260], and for the degradation of phenol [261]. This hybrid also has potential for the fabrication of biogas sensors and electrochemical sensors.…”
Section: Reviewmentioning
confidence: 99%
“…The higher apparent quantum efficiency of 18.5% was obtained over RB sensitized graphene sheets with dispersed Pt nanoparticles under visible light irradiation of 550 nm [86]. Graphene is known as a promising material in designing hybrids for photocatalysis [77,88]. Besides improving electron transfer and charge separation, dispersible graphene sheets provide great interfaces for highly dispersing nanoparticles, enhancing hydrogen generation compared to GO and MWCNT.…”
Section: Role Of Co-catalystmentioning
confidence: 99%